Communication and Conflict in the Evangelical Community: Analysis of the Relations Between Baptists and Pentecostals in the USSR in the Second Half of the 20th Century. (14th December 2016) - Beliakova, Nadezhda; Kliueva, Vera
Abstract: This article analyses a variety of communicative strategies between Baptists and Pentecostals in communities registered in the All-Union Council of Evangelical Christians and Baptists. Although both denominations had a strong religious identity, the expansion of Pentecostals led to conflicts in the intra-community communication. By creating an alternative religious community Pentecostals produced their own hierarchical authority, which included women possessing special "spiritual gifts".